Increased double strand breaks in diabetic β-cells with a p21 response that limits apoptosis - Tay, Vanessa Shi Yun (2021)
DNA damage and DNA damage response (DDR) pathways in β-cells have received little attention especially in the context of type-2 diabetes. We postulate that p21 plays a key role in DDR by preventing apoptosis, associated through its overexpression triggered by DNA stand breaks (DSBs). Our results show that β-cells from chronic diabetic mice had a greater extent of DSBs as compared to their non-diabetic counterparts. Comet assays and nuclear presence of γH2AX and 53bp1 revealed increased DNA DSBs in 16 weeks old (wo) db/db β-cells as compared to age matched non-diabetic β-cells. Our study of gene expression changes in MIN6 cell line with doxorubicin (Dox) induced DNA damage, showed that the DDR was similar to primary β-cells from diabetic mice. There was significant overexpression of DDR genes, gadd45a and p21 after a 24-hr treatment. Western blot analysis revealed increased cleaved caspase3 over time, suggesting higher frequency of apoptosis due to Dox-induced DNA strand breaks. Inhibition of p21 by pharmacological inhibitor UC2288 under DNA damage conditions (both in Dox-induced MIN6 cells and older db/db islets) significantly increased the incidence of β-cell apoptosis. Our studies confirmed that while DNA damage, specifically DSBs, induced p21 overexpression in β-cells and triggered the p53/p21 cellular response, p21 inhibition exacerbated the frequency of apoptosis.